Basic Work Analysis Of Mechanical And Electrical Manufacturing, Installation And Construction Technology - Jiang, Lin; Wang, Jiajun (Journal of Theory and Practice of Engineering Science, 2024)
The reasonable implementation of mechanical and electrical manufacturing, installation and construction technology has an important impact on the orderliness and rationality of construction engineering construction. Due to the great complexity of mechanical and electrical manufacturing and installation, the installation and construction technology should be rationally selected in order to ensure the installation quality. In addition, construction cost, construction schedule, construction safety and construction quality should also be considered in the mechanical and electrical manufacturing and installation construction tasks, so as to improve the quality level of installation engineering. This article is mainly to analyze and study the basic work of mechanical and electrical manufacturing and installation construction technology.